(untitled) (Texas Journal of Engineering and Technology, 2026)
This article presents scientific and practical recommendations for identifying aspects, assessing their significance levels, and reducing negative impacts by creating an environmental risk management organization standard in the production processes of plastic and rubber components for the automotive industry. During the study, an environmental profile for plastic, rubber, and dyeing workshops was formed based on the requirements of the international ISO 14001 standard